Technical Study of the Performance of Liquid Sulfur Combustion in the Process of Sulfuric Acid Production - Suwarmin Suwarmin; Bambang Sudarmanta; Nur Ikhwan (JMES: The International Journal of Mechanical Engineering and Sciences, 2018)
The production process of sulfuric acid is carried out in stages from combustion of liquid sulfur to SO$_2$, then to SO$_3$ and dissolving SO$_3$ in aqueous sulfuric acid solution to concentrated sulfuric acid (high concentration). The success of the production process is very dependent on the initial combustion process into SO$_2$, physical parameters on the liquid sulfur characteristics and the nozzle geometry. The process of burning liquid sulfur depends on the pattern of atomization in the geometry of the nozzle and its fluid characteristics. Liquid sulfur is included in non-newtonian fluids, so the atomization process requires an understanding of its characteristics. The atomization mechanism at the nozzle depends on 3 parameters including viscosity, surface tension and density. In non- Newtonian fluid 3 parameters are sensitive to changes in pressure and temperature. In terms of the geometry of the tip nozzle diameter, smaller diameter, the atomization process is better, but a decrease in temperature will cause clogging. Individual installation of temperature and pressure sensors for each nozzle is chosen so that the atomization of each nozzle can be controlled.